Torque to counter-current direction driving low frequency tearing modes in JT-60U. (23rd September 2021) - Bando, T; Honda, M; Inoue, S; Yoshida, M; Matsunaga, G; Isayama, A; Takechi, M; Shinohara, K; Sumida, S
Abstract: In the JT-60U tokamak, low frequency modes (LFMs) have been reported recently when the m / n = 2/1 neoclassical tearing mode grows sufficiently. LFMs show the low mode frequencies (<20 Hz) with the rotation direction to the counter-current direction (ctr-direction) toroidally, even if strong injection power to the co-current direction (co-direction) is applied by tangential neutral beam injections. As a candidate to drive the rotation to the ctr-direction, the neoclassical toroidal viscosity (NTV) torque is investigated in this study. Indeed, when a LFM is observed, the estimated 'offset velocity' of the NTV torque is larger than the observed toroidal velocity around the q = 2 surface and results in the torque to the ctr-direction (ctr-torque). The torque balance between the NTV torque and the torque induced by the eddy current on the resistive wall is investigated. It is found that the rotation to the ctr-direction having the low mode frequency is obtained as the result of the ctr-torque to the offset velocity. Our investigation suggests the requirement to include the NTV torque in the modeling on the mode locking of neoclassical tearing modes in tokamaks.